2021
DOI: 10.1111/cpr.13016
|View full text |Cite
|
Sign up to set email alerts
|

Special AT‐rich sequence‐binding protein 2 (Satb2) synergizes with Bmp9 and is essential for osteo/odontogenic differentiation of mouse incisor mesenchymal stem cells

Abstract: Objectives Mouse incisor mesenchymal stem cells (MSCs) have self‐renewal ability and osteo/odontogenic differentiation potential. However, the mechanism controlling the continuous self‐renewal and osteo/odontogenic differentiation of mouse incisor MSCs remains unclear. Special AT‐rich sequence‐binding protein 2 (SATB2) positively regulates craniofacial patterning, bone development and regeneration, whereas SATB2 deletion or mutation leads to craniomaxillofacial dysplasia and delayed tooth and root development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Herein, it was also proved that SCAPs and BMP9 could be implanted into the scaffold together to promote vertical new bone regeneration. Other studies have also demonstrated the osteogenic effect of BMP9 (Bharadwaz and Jayasuriya, 2021;Chen et al, 2021;Yang et al, 2023). BMP9 can stimulate DNA (deoxyribonucleic acid) synthesis and cell replication, thus promoting the directional differentiation of stem cells into osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, it was also proved that SCAPs and BMP9 could be implanted into the scaffold together to promote vertical new bone regeneration. Other studies have also demonstrated the osteogenic effect of BMP9 (Bharadwaz and Jayasuriya, 2021;Chen et al, 2021;Yang et al, 2023). BMP9 can stimulate DNA (deoxyribonucleic acid) synthesis and cell replication, thus promoting the directional differentiation of stem cells into osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“… 83 SATB2 is found to enhance the expression of bone matrix proteins and osteogenic transcription factors in MSCs. 84 Besides, MSCs effectively differentiate into osteoblasts and mineralize through IL-1/Wnt-5a/Ror2 pathway, confirmed by enhanced ALP activity and expression of Runx2. 85 In addition, MSCs indirectly promote bone regeneration by inhibiting the function of osteoclasts.…”
Section: Msc Transplantationmentioning
confidence: 93%
“…Bone morphogenetic protein 9 (BMP9, also known as Gdf2 ), a member of the transforming growth factor (TGF)-β superfamily, is mainly produced by the liver. In our previous study, we reported that BMP9 is one of the most potent BMPs in inducing osteogenic/odontogenic differentiation of mesenchymal stem cells (MSCs) [ 16 18 ]. Furthermore, it has been reported that BMP9 plays a critical role in hepatic glucose production, lipid metabolism, and fibrosis, including lung, liver, and cardiac fibrosis [ 19 – 21 ].…”
Section: Introductionmentioning
confidence: 99%